Collective Moral Obligations: 'We-Reasoning' and the Perspective of the Deliberating Agent. (9th March 2019) - Schwenkenbecher, Anne
Abstract: Together we can achieve things that we could never do on our own. In fact, there are sheer endless opportunities for producing morally desirable outcomes together with others . Unsurprisingly, scholars have been finding the idea of collective moral obligations intriguing. Yet, there is little agreement among scholars on the nature of such obligations and on the extent to which their existence might force us to adjust existing theories of moral obligation. What interests me in this paper is the perspective of the moral deliberating agent who faces a collective-action problem, i.e., the type of reasoning she employs when deciding how to act. I hope to show that agents have collective obligations precisely when they are required to employ 'we-reasoning', a type of reasoning that differs from I-mode, best-response reasoning. More precisely, two (or more) individual agents have a collective moral obligation to do x if x is an option for action that is only collectively available and each has sufficient reason to rank x highest out of the options available to them.